2019
DOI: 10.1130/g46602y.1
|View full text |Cite
|
Sign up to set email alerts
|

A shallow origin for diamonds in ophiolitic chromitites: REPLY

Abstract: We are grateful to Massonne (2019) and Yang et al. (2019) for their constructive Comments to our recent publication (Farré-de-Pablo et al., 2018). We appreciate their interest in discussing our results and interpretations, which confirm that our work is a benchmark for future research. We are pleased to have the opportunity to address in further detail their concerns on the natural origin of the reported microdiamonds in Tehuitzingo, Mexico, chromitites (Massonne, 2019), as well as their geological meaning (Ya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Recently, the finding of in situ diamond in chromite-hosted fluid inclusions from ophiolitic chromitites by Farré- de-Pablo et al, (2019a) provided the first evidence for empirical (Simakov et al, 2015(Simakov et al, , 2020, experimental (Simakov et al, 2008) and theoretical (Manuella, 2013;Simakov, 2018) work on low pressure growth of diamond. However, the debate on the natural origin of diamond continued (e.g., Farré-de-Pablo et al, 2019b;Massonne, 2019;Yang et al, 2019). In this regard, Litasov et al (2019a,b) have recently claimed that most diamonds, if not all, from ophiolitic rocks are not natural but instead have a synthetic origin, and emphasised the need to identify diamond below the polished surface of the host mineral.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the finding of in situ diamond in chromite-hosted fluid inclusions from ophiolitic chromitites by Farré- de-Pablo et al, (2019a) provided the first evidence for empirical (Simakov et al, 2015(Simakov et al, , 2020, experimental (Simakov et al, 2008) and theoretical (Manuella, 2013;Simakov, 2018) work on low pressure growth of diamond. However, the debate on the natural origin of diamond continued (e.g., Farré-de-Pablo et al, 2019b;Massonne, 2019;Yang et al, 2019). In this regard, Litasov et al (2019a,b) have recently claimed that most diamonds, if not all, from ophiolitic rocks are not natural but instead have a synthetic origin, and emphasised the need to identify diamond below the polished surface of the host mineral.…”
Section: Introductionmentioning
confidence: 99%
“…The controversial genetic interpretation of diamond, chromitite and their host peridotite in various ophiolites not only includes the aforementioned four main models but also involves other viewpoints, e.g., UHP and highly reduced mineral assemblages possibly formed by lightning strikes [145], contamination by artificial abrasive materials [146], or formed during serpentinization under low pressure [39]. These issues have recently been hotly debated [147][148][149][150]. It is noted that Farré-de-Pablo et al (2018) reported in situ microdiamonds (diameter = 1-8 µm) in chromite from the Tehuitzingo chromitite in the Acatlán Orogenic Belt in southern Mexico.…”
Section: Controversy and Future Perspectivesmentioning
confidence: 99%
“…Farré-de-Pablo et al (2019) replied that they had not found UHP minerals other than diamond in the Tehuitzingo chromitites, serpentinized peridotites and other rocks from the Acatlán Complex and claimed that the metamorphism of the Acatlán Complex did not even reach the stability of coesite. They argued that the aforementioned abundant so-called UHP and highly reduced minerals or oriented lamellae of Cpx in chromite developed during cooling and serpentinization rather than under UHP conditions [147].…”
Section: Controversy and Future Perspectivesmentioning
confidence: 99%